Socio-geographical aspects of the development of the intangible cultural heritage of the Odessa region - Yaromenko, P.; Yurash, E. (Journal of Education, Health and Sport, 2025)
The article examines the socio-geographical aspects of the development of the intangible cultural heritage of the Odessa region. The emphasis is on the territorial differentiation of cultural practices, the preservation of ethno-cultural diversity and the role of intangible resources in the formation of regional identity. The key manifestations of intangible heritage are identified - multinational traditions of the Black Sea region, unique musical and gastronomic practices, folk crafts and rituals. The impact of urbanization processes, tourism development and decentralization on the transformation of intangible cultural heritage is analyzed. The importance of intangible resources as a factor in the sustainable development of territories and the integration of the Odessa region into the European cultural space is substantiated.